1998
DOI: 10.1159/000028693
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendoscopic Third Ventriculostomy in Patients Less than 1 Year Old

Abstract: A series of neuroendoscopic third ventriculostomies in children less than 1 year old is reported. Twenty-seven patients underwent the procedure with 21 (77%) failing within a mean of 1.36 months of the procedure. Nineteen were subsequently shunted. The presence or absence of flow through the ventriculostomy and the size of the lateral ventricles on post-operative imaging were not an indicator of success or failure. Only 4 (15%) had a complication of the procedure. Although the majority fail, approximately 1/3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
117
1
6

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(133 citation statements)
references
References 16 publications
9
117
1
6
Order By: Relevance
“…The complication rate of 11% encountered in this study fits well within the 6 to 20% range of complication rates reported in the literature (17). Although several serious and fatal complications have been reported including intraoperative venous or arterial bleeding, seizures, CSF leakage, infection, oculomotor nerve palsy, bradycardia, temperature regulation disturbance, diabetes insipidus, syndrome of inappropriate antidiuretic hormone, basilar artery perforation or traumatic aneurysm, subarachnoid, and subdural hematoma (2, 3,4,10,11,14,23,25), the complications of ETV in the majority of cases are usually clinically insignificant.…”
Section: A B C Azab W Et Al: Preoperative Endoscopic Third Ventriculsupporting
confidence: 85%
“…The complication rate of 11% encountered in this study fits well within the 6 to 20% range of complication rates reported in the literature (17). Although several serious and fatal complications have been reported including intraoperative venous or arterial bleeding, seizures, CSF leakage, infection, oculomotor nerve palsy, bradycardia, temperature regulation disturbance, diabetes insipidus, syndrome of inappropriate antidiuretic hormone, basilar artery perforation or traumatic aneurysm, subarachnoid, and subdural hematoma (2, 3,4,10,11,14,23,25), the complications of ETV in the majority of cases are usually clinically insignificant.…”
Section: A B C Azab W Et Al: Preoperative Endoscopic Third Ventriculsupporting
confidence: 85%
“…Other works, such as those of Buxton et al [60], Kadrian et al [61] and Koch-Wiewrodt et al [62] as referred to in Spennato et al [56], reported the opposite extreme of success rates below 30% in infants and considered an age under one year to be a contraindication for ETV.…”
Section: Discussionmentioning
confidence: 95%
“…1,3 The success rate of ETV/CPC in children younger than 2 years varies from less than 50% to as high as 80% depending on the etiology of hydrocephalus. 1,4,13 In a large cohort of Ugandan children with postinfectious hydrocephalus, Warf found that adding CPC to ETV increased the success rate from 47% to 66%. 23 In the existing literature, the success rate of ETV/CPC for the PHHP population is reported to be 10%-44%.…”
mentioning
confidence: 99%